Echocardiographic Detection of Cardiac Dysfunction in Childhood Cancer Survivors: How Long Is Screening Required?. Issue 12 (6th July 2015) - Ramjaun, Aliya; AlDuhaiby, Eman; Ahmed, Sameera; Wang, Lisa; Yu, Eric; Nathan, Paul C.; Hodgson, David C.
<x xml:space="preserve">Abstract</x> Background Childhood cancer survivors treated with anthracycline chemotherapy are at an increased risk of long‐term cardiac toxicity, and guidelines recommend that exposed survivors undergo echocardiography every 1–5 years. However, it is unclear whether survivors should undergo echocardiographic screening indefinitely, or if a period of echocardiographic stability indicates that screening is no longer necessary. The objective of this study was to evaluate the outcomes of echocardiographic screening to aid in the refinement of existing guidelines. Methods We retrospectively analyzed the results of echocardiographic screening in a cohort of adult survivors of childhood cancer treated with anthracyclines and/or cardiac radiation therapy. Interval regression analysis was performed to identify predictors of single‐episode or sustained abnormal echocardiograms. Results The cohort constituted 333 survivors, with median follow‐up time of 15.8 years post‐treatment (range: 5.0–47.9), and median age at treatment of 8 years (range: 1.5–18). Forty‐nine survivors had an abnormal echocardiogram (14.7%), and 29 (8.7%) had reproducible abnormal findings. An ongoing continual increase in the incidence of sustained echocardiographic abnormality was seen among patients treated with >250 mg/m2 doxorubicin at age <5 years, reaching 43% by 20 years of therapy. In contrast, no sustained abnormal echocardiographic findings arose after 10 years of therapy in survivors treated with <250 mg/m2 at age ≥5 years. Conclusions Single‐episode echocardiographic abnormalities are often not reproduced in subsequent evaluations. The duration of echocardiographic screening for childhood cancer survivors should be reassessed for patients who received lower doses of anthracycline after age 5. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.